2020
DOI: 10.1186/s12881-020-01083-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel ECHS1 mutations in Leigh syndrome identified by whole-exome sequencing in five Chinese families: case report

Abstract: Background: Short-chain enoyl-CoA hydratase deficiency (ECHS1D), also known as ECHS1 deficiency, is a rare inborn metabolic disorder with clinical presentations characterized by Leigh syndrome (LS). Thirty-four different pathogenic mutations have been identified from over 40 patients to date. Case presentation: Here, we report five Chinese patients with clinical syndromes typified as LS. Despite different initial symptoms, all patients presented developmental regression, dystonia, common radiological features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The variable distribution of defects across East Asian and European cohorts suggests that genetic defects may vary based on ethnicity or between populations, such as due to founder mutations as previously described for ECHS1 and GTPBP3 in Chinese patients. 30,31 We, however, found only limited evidence for the contribution of founder variants to disease, with only 5 variants of potential founder status identified in our Chinese LS population. LS was primarily clinically defined in the pregenome area, however, we know today that LS comprises a large heterogeneous group of approximately 100 distinct rare genetic disorders.…”
Section: Discussionmentioning
confidence: 55%
“…The variable distribution of defects across East Asian and European cohorts suggests that genetic defects may vary based on ethnicity or between populations, such as due to founder mutations as previously described for ECHS1 and GTPBP3 in Chinese patients. 30,31 We, however, found only limited evidence for the contribution of founder variants to disease, with only 5 variants of potential founder status identified in our Chinese LS population. LS was primarily clinically defined in the pregenome area, however, we know today that LS comprises a large heterogeneous group of approximately 100 distinct rare genetic disorders.…”
Section: Discussionmentioning
confidence: 55%
“…1 Since then 58 patients have been identified with it worldwide. 4,[7][8][9][10][11][12] Here, we presented the 59th case of a patient with ECHS1 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intermediate and mild cases usually have normal laboratory values. A review of the literature 1‐4,6‐29 revealed 67 patients with most suffering the early onset presentation. Average age at death was 28.0 + 43.8 months (range 16 h to 156 months) for 27 early onset patients (age <12 months) for whom age at death was reported.…”
Section: Introductionmentioning
confidence: 99%